Tumor associated carbonic anhydrase inhibitors: Rational approaches, design strategies, structure activity relationship and mechanistic insights - Sridhar Goud Nerella; Pavitra S. Thacker; Mohammed Arifuddin; Claudiu T. Supuran (Elsevier, 2024)
The emergence of tumor-associated human carbonic anhydrases (hCA) as promising therapeutic targets has urged rigorous research into the development of potent and selective hCA IX and XII inhibitors. Rationalization of targeting tumor-specific hCA isoforms is a major challenge that requires a comprehensive understanding of the interactions between inhibitors and the dynamic hCA active site. The benzenesulfonamides and its bioisosteres are currently being used clinically as inhibitors of various hCA isoforms through classical inhibitory mechanism. In addition, several other chemotypes have also been developed with improved potency and selectivity through non-classical inhibitory mechanisms. Coumarin and its derivatives represent highly selective and potent inhibitors of hCA IX and XII. Recently, various other pharmacophores were also proven to have a strong selectivity and potency against hCA IX and XII including pyrazole, 1,2,3-triazole, 4-thiazolidinone, and thiourea. This review navigates through understanding the role of hCA IX and XII in cancer biology, encompassing different inhibition approaches, strategic design methodologies, recent advancements in the rational design of hCA inhibitors, exploration of structure-activity relationships, in-depth mechanistic insights, and PET imaging applications for in vivo visualization of target enzymes.